(untitled) - Arthur Israel Volgel (London, 1989)
The book presents the basic theory underlying chemical processes alongside coverage of more practical subjects, including the taking of representative samples, statistical treatment of data and the types of equipment required. Its appendices present additional data routinely used by analysts, including statistical tables, pH values of buffer solutions and solubilities of common reagents
Keywords: chemistry, analytic - quantative,chemistry, organic